Teknik dan Prosedur Asosiasi Bebas dan Interpretasi dalam Konseling Psikoanalisa - Habsy, Bakhrudin All; Azizah, Mutiara; Syahputra, Mohammad Rizky Adi; Yuliana, Tabita Tindie (TSAQOFAH, 2024)
Psychoanalytic theory is a theory that attempts to explain the nature and development of personality. The classic psychoanalyst is Sigmund Freud, Freud initially developed his theory about personality structure and the causes of mental disorders. The main elements of this theory are motivation, emotions, and other aspects of consciousness. The purpose of this article is to know Techniques and Procedures for Free Association and Interpretation in Psychoanalytic Counseling. The method used in this research is qualitative with a literature study, starting with written material that is considered the most relevant. The results of this research include, namely (1) Basic procedures for free association counseling techniques, (2) procedures for interpretation counseling techniques, (3) Steps for free association, (4) Steps for interpretation counseling techniques.